Statistics for engineering problem solving - Vardeman, Stephen B. (PWS Foundations in engineering series., 1994)
This innovative text uses real data and scenario examples and a chapter-length case study (Chapter 11) to teach students how apply statistical methods to the solution of engineering problems. Employing a practical, applied approach, the author encourages students to do statistics by carrying data collection and analysis projects all the way from problem formulation to preparation of professional technical reports. The authors goals in writing this text are to stress the engineering problem-solving implications of statistical references, and to foster development of scientific and statistical thought processes in the reader. Mathematical theory is not presented as an end in itself, but rather as a means to more effective engineering practice.